Pengaruh Brand Experience Terhadap Brand Loyalty Pada Restoran - Wiastuti, Rachel Dyah; Sigar, Gavin (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2021)
The purpose of this study is to determine the influence of brand experience towards brand loyalty at Restaurant Pondok 18 Pontianak. This research used quantitative approach. Primary data was collected through direct field survey using questionnaire with 5-point Likert scale and close ended questions. Sample of this research was 100 dine- in customers of Restaurant Pondok 18 Seafood Pontianak: calculated with Slovin formula and collected by random sampling. Data was analyzed with descriptive statistic, correlation, and regression analysis. The result indicates that there was a significant influence between brand experience and brand loyalty with value of 42.3%. Brand experience and brand loyalty also have a strong positive correlation. Furthermore, sensory experience become the most determined brand experience dimension compared to affective, behavioral, and intellectual experience. Meanwhile, attitudinal loyalty shows bigger determinant than behavioral loyalty in term of brand loyalty. Thus, restaurants premises are strongly suggested to improve company logo to enhance customer interest, to ensure having a membership program, and to maintain food quality. Keyword: brand experience, brand loyalty, restaurant, sensory experience